Implementation of Islamic Economic Management at Kindergarden Phatnawitya School Thailand - Noni Putri (Journal of Contemporary Islamic Primary Education, 2023)
The purpose of this research is to understand the concept and application of Islamic education and Islamic business management in Southeast Asia, the research area is Islamic education and Islamic business management in Indonesia and Thailand. This study uses an academic approach with a historical perspective. Using this process and conceptualizing and implementing Islamic education and Islamic business management in Southeast Asia (in Indonesia and Thailand), much of the existing and developed theory has to be clarified. The results of the study show that there are similarities in the concept and implementation of Islamic education and Islamic business management in Indonesia and Thailand which are geographically close to each other so that they can experience the same historical moment that encompasses them to the stage of civilization. World time Another thing that is similar is that the two countries are in the ongoing development of the Islamic economy, even today the development of the Islamic economy in Thailand is very rapid, especially at Kindegarden Phatnawitya School.